The state as a shareholder in cases of reflective loss deriving from commercial activities in international investment arbitration - Ripson, Coen Petrus Johannes (Department of Commercial Law, 2026)
The purpose of the present thesis is to provide an overview of the legal position of state shareholders in International Investment Arbitration in case of shareholders' claims for reflective loss deriving from commercial investments. The reflective loss principle refers to direct claims brought by shareholders who have suffered a reduction in their shares' value due to actions of the company or a third party. Claims for reflective loss raised by private investors against the host state are often admissible in International Investment Arbitration, although they are generally not accepted under domestic law. The assessment of the treatment of state shareholders' claims for reflective loss under the current investment treaties, with the focus placed on the procedural restrictions, deriving mostly from the ICSID Convention at the arbitration stage, demonstrates an imbalance between private and state shareholders when they both act as claimants. The reasons for the imbalance lie in restrictions for state shareholders originating from: a) the protection scope and aim of International Investment Arbitration, b) the limited amount of fora available to state investors and c) the insufficient protection of state investors under the investment treaties. Based on the existing international investment law and jurisprudence as well as on the domestic law of 10 jurisdictions, the current (international) legal framework on the admissibility of claims for reflective loss made by the state shareholder against the host state is being presented. The potential impact on the host state is considered in relation to the enhancement of the position of the state as a claimant in International Investment Arbitration. In terms of a holistic approach to the issue, the risks that commercial investments made by state entities impose on host states are also being analysed. The identified risks for the host state derive from a) public interest concerns and b) the state shareholder's immunity from execution in case the host state wins the case and needs to enforce the arbitral decision on costs against the state shareholder.